Rainfall models in the verification of the existing concept of urban rainwater and snowmelt drainage system – case study - Hładki, Piotr; Miszta-Kruk, Katarzyna (Instal, 2025)
The proper design of the stormwater drainage system, due to the irregular and random nature of rainfall, constant changes in the catchment structure and, consequently, the nature of runoff, is of concern. Short-lived and heavy rains are increasingly contributing to the overloading of sewer systems in cities, leading to failures and even urban flooding. Existing drainage concepts in many cities were created based on historically recommended guidelines and previously used design methods, tested against the latest rainfall data, may not stand the test of time and fail to meet the challenges posed by modern rainwater and snowmelt drainage systems. The article attempts to evaluate a section of the stormwater drainage network of one city in Poland, which is being successively implemented based on an existing concept created in 2014, more than 10 years ago. The functioning of the network was analysed in a model created in the Storm Water Management Model (SWMM) program by loading it with four rainfall scenarios with probability of exceedance p = 20% (frequency of occurrence C = 5 years, for urban areas according to PN-EN 752:2017-06) developed based on historical and current rainfall intensity data. Analysed simulations indicated conduits reaching maximum filling and thus acting pressurised, the locations and moments of network overflows changing depending on the adopted rainfall model. As the model has not been calibrated based on real data (flows in the conduits, roughness), the results should be considered in an illustrative character.